Improving Creative Thinking Ability of Prospective Elementary School Teachers through Read-Answer-Discuss-Explain-and Create (RADEC) Project-Oriented Learning Model - Septinaningrum, Septinaningrum; Sopandi, W; Agustin, M; Gumala, Y; Anggraeni, P; Rahayu, A H; Tursinawati1, Tursinawati; Nugraha, L; Rohman, Khabibur (International Conference on Elementary Education, 2020)
The objective of this research was to describe the improvement of the creative thinking ability of prospective elementary school teachers through project-oriented ReadAnswer-Discuss-Explain-and Create (RADEC) project-oriented learning model. The researcher applied the mixing method consisting of descriptive qualitative research. The design of this research was pre-experiment one group pre-test post-test design subjects. The instrument of the research consisted of the test, observation sheet, interview, and field notes. The result of the research showed that the students' creative thinking ability increased significantly. The aspect of fluency increased by 40.1%, flexibility 43.81%, originality 37%, and elaboration increased by 45.04%. Therefore, it can be concluded that the RADEC project-oriented learning model can significantly improve the students' creative thinking ability